Functional electron paramagnetic resonance imaging of ischemic rat heart: Monitoring of tissue oxygenation and pH. Issue 1 (24th August 2015) - Gorodetsky, Artem A.; Kirilyuk, Igor A.; Khramtsov, Valery V.; Komarov, Denis A.
Abstract : Purpose: Electron paramagnetic resonance (EPR) imaging in the spectral‐spatial domain with application of soluble paramagnetic probes provides an opportunity for spatially resolved functional measurements of living objects. The purpose of this study was to develop EPR methods for visualization of oxygenation and acidosis of ischemic myocardium. Methods: EPR oxygen measurements were performed using isotopically substituted 2 H, 15 N‐dicarboxyproxyl. The radical has an EPR line width of 320 mG and oxygen‐induced line broadening of 0.53 mG/mm Hg, providing oxygen sensitivity down to 5 μM. pH measurements were performed using previously developed pH‐sensitive imidazoline nitroxide. The radical has an EPR spectrum with pH‐dependable hyperfine splitting, pK = 6.6, providing pH sensitivity of approximately 0.05 U in the physiological range. Results: EPR imaging of isolated and perfused rat hearts was performed in the two‐dimensional + spectral domain. The spatial resolution of the measurements was about 1.4 mm. Marked tissue hypoxia was observed in the ischemic area of the heart after occlusion of the left anterior descending coronary artery. Tissue oxygenation was partly restored upon reperfusion. EPR mapping of myocardial pH indicated acidosis of the ischemic area down to pH 6.7–6.8. Conclusion: This study demonstrates the capability of low‐field EPR and the nitroxide spin probes for mapping of myocardial oxygenation and pH. The developed approaches might be used for noninvasive investigation of microenvironment on living objects. Magn Reson Med 76:350–358, 2016. © 2015 Wiley Periodicals, Inc.